The beautiful butcher and the young afflicted with coprophilia. Science, method and ethics of psychoanalysis - Ponce Bogino, Héctor (2015)
We are going to reflect on the epistemology and methodology of Freud, furthermore about how evaluate ethically the recent findings of the private correspondence of Freud in which the recovery of some patients is denied who have been treated by Freud.The objective is a personal evaluation; the sources are bibliographical; and the conclusions are: 1) In Epistemology, the psychoanalysis is located in human sciences and Freud created a valuable theory of mind as a carrier of many wills that allows new forms of retrospect. 2) In methodology, the psychoanalysis is enriched if, instead of appeal to the “laws of the unconscious”, is inspired in hermeneutics. 3) In Ethics, Freud was not truthful, when he presented as culminated process, many patients who therapeutically do not improve, and the psychoanalytical community has not acted properly.